MAKNA DAN FUNGSI TRADISI SANGGRING DI MASYARAKAT LAMONGAN - Rahayu, Ela Puji (Program Studi Sejarah Peradaban Islam, 2024)
Sanggring is a sacred and holy tradition for the Tlemang community. This sacred and holy tradition when cooking Sanggring men and without being tasted, can be tasted when finished cooking and served to invited guests. That way, the sacredness resulted in many questions but until now there are still some who do not know the answers. Such as the meaning and function of the Sanggring ritual performed every year on 24-27 Jumadilawal / Rabiul Awal, the meaning of each seasoning and the flavors created from Sanggring dishes. This is because people do not pay attention to the meaning and significance of the Sanggring tradition in detail. This article aims to explore this phenomenon through research located in Tlemang Village, Ngimbang District, Lamongan Regency, East Java. This research seeks to discuss descriptive qualitative method with a field study approach and literature. Data obtained from observations and interviews are used to collect data related to the meaning and function of the Sanggring tradition in the Tlemang community. data analysis using the phenomenological method of Alfred Schutz's perspective provides basic ideas that form the basis of a social school of thought that emphasizes understanding that is able to understand the meaning of social action. The results of this study are 1) The Sanggring ritual has meaning and function from the first day to the fourth day. 2) Each Sanggring seasoning has a meaning and function in the ritual. The myth of Sanggring can create sweet, spicy, sweet and savory flavors that have their own meaning and function.